Psychotic-like experiences in help-seeking adolescents: Dimensional exploration and association with different forms of bullying victimization – A developmental social psychiatry perspective. (December 2017) - Catone, Gennaro; Marotta, Roberta; Pisano, Simone; Lennox, Belinda; Carotenuto, Marco; Gritti, Antonella; Pascotto, Antonio; Broome, Matthew R
Background: Psychotic-like experiences (PLEs) are common in the general population and increase the risk of psychotic disorders. Adolescents are a high-risk group of this condition. Stressful events, such as bullying, have a role in the onset of PLEs. This study has several aims: (1) to assess PLEs in adolescents seeking help from a Child and Adolescent Mental Health Service, (2) to assess the association of PLEs with specific bullying victimization and (3) to assess difference in PLEs and victimizations by sex and age. Methods: Participants were help-seeking (HS) adolescents initially screened for PLEs. They completed an assessment including characteristics of PLEs and bullying victimization. We paid particular attention to different kinds of PLEs and victimization. Results: In total, 50 PLE-positive adolescents screened from 324 HS adolescents (15.4%) constituted the sample. Paranoia and verbal bullying were the PLEs and form of victimization most represented, respectively. Verbal bullying was strongly associated with paranoia (odds ratio (OR): 4.40, confidence interval (CI): 2.8−5.9, p < .001). Results remained significant after controlling for confounder (socio-demographic, anxiety, depression and for the latter analysis also other forms of victimization). Furthermore, social manipulation showed a strong association of paranoia and physical bullying with grandiosity. Verbal bullying was also associated with psychotic negative symptoms, but controlling for emotional symptoms and other victimization led to a reduction in the effect. Men were more involved in physical victimization and experienced grandiosity; on the contrary, late adolescents were most involved in social victimization and negative psychotic symptoms Conclusion: PLEs are relevant in HS adolescents. Bullying victimization interacts with the onset of these phenomena. In particular, verbal bullying predicted paranoia onset significantly.